Solid electrolyte membrane and preparation method thereof, lithium ion battery

By mixing a halide solid electrolyte with a specific Young's modulus with a second electrolyte with a good fluidity, the solid electrolyte membrane is compressed and prepared, which solves the problem of insufficient membrane density and conductivity in the prior art, and achieves efficient lithium ion transmission and battery circulation performance improvement.

CN117878388BActive Publication Date: 2025-03-21QINGTAO (KUNSHAN) ENERGY DEV CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311803285.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-26
Publication Date
2025-03-21
Estimated Expiration
2043-12-26

AI Technical Summary

Technical Problem

It is difficult to prepare solid electrolyte membranes with high ionic conductivity and high mechanical strength in the prior art, and cannot effectively match the low internal resistance and excellent cycling performance of the battery system.

Method used

The solid electrolyte membrane is prepared by mixing a halide solid electrolyte with a specific Young's modulus with a second electrolyte with a good fluidity. The ionic conductivity of the second electrolyte is greater than that of the first electrolyte, and a continuous phase can be formed, which improves the density of the film and the lithium ion transmission rate.

Benefits of technology

It improves the density and ionic conductivity of the solid electrolyte membrane, reduces the porosity and battery internal resistance, and significantly improves the cycling performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_6
    Figure SMS_6
Patent Text Reader

Abstract

The present application relates to a solid electrolyte membrane and a preparation method thereof, and a lithium-ion battery, including a first electrolyte and a second electrolyte; wherein the first electrolyte is a halide solid electrolyte with a Young's modulus of <100 GPa; the ionic conductivity of the second electrolyte is greater than the ionic conductivity of the first electrolyte; and the liquid index of the second solid is >1. The second electrolyte of the present application can form a continuous phase, and after being mixed with the first electrolyte, the density of the prepared solid electrolyte membrane is improved, and it has a higher conductivity. At the same time, the contact state between the solid electrolyte membrane and the electrode is improved, the internal resistance of the prepared battery is reduced, and the cycle performance is significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a solid electrolyte membrane and a preparation method thereof, and a lithium ion battery. Background Art

[0002] Solid-state batteries have become one of the main directions of future battery development due to their advantages such as high safety and high energy density. As the core component of solid-state batteries, solid electrolytes play a role in transferring lithium ions between the positive and negative electrodes, and therefore have received widespread attention.

[0003] Solid electrolytes include sulfide solid electrolytes, oxide solid electrolytes, borohydride solid electrolytes, polymer solid electrolytes and halide solid electrolytes, etc. Among them, halide solid electrolytes have become the focus of solid electrolyte research due to their advantages such as high ion conductivity, high chemical stability and easy preparation.

[0004] The preparation of solid electrolyte membranes using solid electrolytes as raw materials is a hot topic in this field, especially the preparation of halide solid electrolyte membranes. However, how to prepare solid electrolyte membranes with high ionic conductivity and high mechanical strength to match the requirements of low internal resistance and excellent cycle performance of battery systems is an urgent problem to be solved. Summary of the invention

[0005] Based on this, in order to solve the above problems, the present application provides a solid electrolyte membrane and a preparation method thereof, and a lithium-ion battery to solve the above technical problems.

[0006] According to a first aspect of the present invention, a solid electrolyte membrane is provided, comprising a first electrolyte and a second electrolyte; wherein the first electrolyte is a halide solid electrolyte; the Young's modulus of the first electrolyte is less than 100 GPa; the liquid index of the second electrolyte is greater than 1; and the ionic conductivity of the second electrolyte is greater than the ionic conductivity of the first electrolyte.

[0007] In some embodiments, at the same pressure, the volume deformation of the first electrolyte is smaller than the volume deformation of the second electrolyte.

[0008] In some embodiments, the first electrolyte has a Young's modulus < 45 GPa.

[0009] In some embodiments, the second electrolyte includes Li a M bm N b(1-m) Cl a F 3b , wherein 1.5≤a:b≤3.5, 0≤m<0.7, M includes one of Al and In, and N includes Ga.

[0010] In some embodiments, the porosity φ of the solid electrolyte membrane is <10%.

[0011] In some embodiments, the ionic conductivity of the first electrolyte satisfies .

[0012] In some embodiments, the ionic conductivity of the second electrolyte satisfies .

[0013] In some embodiments, the solid electrolyte membrane has a thickness of 10 μm to 300 μm.

[0014] In some embodiments, the first electrolyte includes Li2ZrCl6 and derivatives of Li2ZrCl6.

[0015] In some embodiments, the derivatives of Li2ZrCl6 include Li 2+4x-ax Zr 1-x A x Cl6; wherein a is the valence state of metal A, 1≤a≤6, x<1, and metal A includes one of Dy, Nb, and Mn.

[0016] In some embodiments, the derivatives of Li2ZrCl6 include Li2ZrCl 6-by B y ; Wherein, b is the valence state of metal B, y≤1, and B is O element or halogen element.

[0017] A second aspect of the present application provides a method for preparing a solid electrolyte membrane, comprising the following steps:

[0018] S1: preparing a first electrolyte.

[0019] S2: preparing the second electrolyte: weighing LiCl, MF3, and NF3, adding them into a ball mill, and forming the second electrolyte by ball milling.

[0020] S3: preparing mixed electrolyte powder: weighing the first electrolyte and the second electrolyte, and ball milling to form mixed electrolyte powder.

[0021] S4: Preparation of solid electrolyte membrane: Mixed electrolyte powder is loaded into a mold and pressed to form a solid electrolyte membrane.

[0022] In MF3, M includes one of Al and In; in NF3, N includes Ga.

[0023] In some embodiments, in the mixed electrolyte powder, the weight ratio of the first electrolyte to the second electrolyte is (1-50): (50-99).

[0024] A third aspect of the present application provides a lithium-ion battery, comprising the solid electrolyte membrane provided by the first aspect or the solid electrolyte membrane prepared according to the preparation method provided by the second aspect.

[0025] The present application obtains a solid electrolyte membrane by mixing a first electrolyte having a specific Young's modulus with a second electrolyte in a fluid state and pressing. The second electrolyte in the prepared solid electrolyte membrane has a certain fluidity and can be used as a mobile phase. The first electrolyte can be better distributed in the second electrolyte alone or continuously. Since the second electrolyte has fluidity, it can better fill the gaps in the first electrolyte during the pressing process, thereby improving the compactness of the solid electrolyte membrane and reducing the porosity. The ionic conductivity of the second electrolyte is greater than the ionic conductivity of the first electrolyte, which can increase the battery capacity of the lithium-ion battery. In addition, the contact area of ​​two adjacent first electrolytes is smaller than the contact area between the first electrolyte and the adjacent second electrolyte. Therefore, the first electrolyte can form a continuous lithium ion transmission path, further improving the ionic conductivity in the lithium-ion battery. DETAILED DESCRIPTION

[0026] References to embodiments of the present application will now be provided in detail, one or more embodiments of which are described below. Each embodiment is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.

[0027] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.

[0028] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0029] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0030] In this article, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left and right endpoints are the same. For example, 100~150 nm means that the units of the left endpoint "100" and the right endpoint "150" are both nm (nanometers).

[0031] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0032] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0033] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, mentioning that the method may also include step (c) means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0034] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0035] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0036] In view of the problems that the halide solid electrolyte membrane in traditional technology cannot achieve good interface contact performance and has large porosity when applied to lithium-ion batteries, this application proposes a solid electrolyte membrane to solve the above-mentioned technical problems of traditional halide solid electrolyte membranes.

[0037] Specifically, the first aspect of the present application provides a solid electrolyte membrane, comprising a first electrolyte and a second electrolyte; wherein the first electrolyte is a halide solid electrolyte; the Young's modulus of the first electrolyte is less than 100 GPa; the liquid index of the second electrolyte is greater than 1, the ionic conductivity of the second electrolyte is greater than the ionic conductivity of the first solid electrolyte, and under the same pressure, the volume deformation of the first solid electrolyte is less than the volume deformation of the second electrolyte.

[0038] In the present application, the volume deformation refers to the difference between the volume V1 of the material before pressure is applied and the volume V2 after pressure is applied.

[0039] It can be understood that the Young's modulus of the first electrolyte is less than 100 GPa, including but not limited to 90 GPa, 85 GPa, 80 GPa, 75 GPa, 70 GPa, 65 GPa, 60 GPa, 55 GPa, 50 GPa, 45 GPa, 35 GPa, 30 GPa, 25 GPa, 20 GPa, 17 GPa, 15 GPa, 10 GPa, 7 GPa, 5 GPa, 3 GPa, 2 GPa, 1 GPa; preferably, the Young's modulus of the first electrolyte is less than 45 GPa; more preferably, the Young's modulus of the first electrolyte is less than 20 GPa; further preferably, the Young's modulus of the first electrolyte is less than 10 GPa.

[0040] In some embodiments, the ionic conductivity of the first electrolyte satisfies Preferably, the ionic conductivity of the first electrolyte satisfies .

[0041] It is understood that the first electrolyte includes Li2ZrCl6 and its derivatives.

[0042] In some embodiments, the derivative of Li2ZrCl6 includes Li 2+4x-ax Zr 1-x A x Cl6; wherein a is the valence state of metal A, 1≤a≤6, x<1, and metal A includes one of Dy, Nb, and Mn. Preferably, the derivative of Li2ZrCl6 is Li 1.9 Nb 0.1 Zr 0.9 Cl6.

[0043] In some embodiments, the derivatives of Li2ZrCl6 include Li2ZrCl 6-by B y ; Wherein, b is the valence state of metal B, y≤1, and B is O element or halogen element.

[0044] In some embodiments, the first electrolyte includes Li3CCl6, wherein C includes one of In, Y, and Sc.

[0045] In some embodiments, the second electrolyte includes Li a M bm N b(1-m) Cl a F 3b , wherein 1.5≤a:b≤3.5, 0≤m<0.7, M includes Al, In, and N includes Ga; the liquid index of the second solid state is greater than 1; preferably, the second electrolyte includes but is not limited to Li2Al 0.3 Ga 0.7 Cl2F3, Li3In 0.6 Ga 0.4 At least one of Cl3F3, Li3GaCl3F3.

[0046] The ionic conductivity of the second electrolyte satisfies , and the ionic conductivity of the second electrolyte is greater than the ionic conductivity of the first electrolyte.

[0047] In the present application, in the preparation of the electrolyte membrane, since the second electrolyte has a larger volume deformation during the pressing process and has good fluidity, it is easy to form a continuous phase, which is beneficial to improving the density of the electrolyte membrane. The first electrolyte is distributed in an independent or connected manner, and lithium ions no longer rely solely on the first electrolyte for transmission, which is beneficial to improving the lithium ion transmission rate of the solid electrolyte membrane. At the same time, the good fluidity of the second electrolyte is beneficial to improving the contact interface between the first electrolyte with a larger Young's modulus and the positive and negative electrodes, thereby effectively reducing the internal resistance of the battery. In addition, due to the excellent mechanical properties of the first electrolyte, it can provide mechanical properties for the electrolyte membrane, control the Young's modulus of the first electrolyte within a certain range, and the first electrolyte also has a certain amount of deformation during the pressing process, which is further beneficial to the improvement of the density of the electrolyte membrane.

[0048] The above is only a possible speculation on the technical solution of the present application and does not constitute a limitation on the protection scope of the present application.

[0049] In the present application, the first electrolyte may provide certain mechanical properties.

[0050] In some embodiments, the porosity φ of the solid electrolyte membrane is less than 10%, including but not limited to 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, and 9%; preferably, the porosity φ of the solid electrolyte membrane is less than 8%; more preferably, the porosity φ of the solid electrolyte membrane is less than 5%.

[0051] In some embodiments, the thickness of the solid electrolyte membrane is 10 μm to 300 μm, including but not limited to 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, 210 μm, 220 μm, 230 μm, 240 μm, 250 μm, 260 μm, 270 μm, 280 μm, 290 μm, 300 μm. Preferably, the thickness of the solid electrolyte membrane is 50 μm to 300 μm; more preferably, the thickness of the solid electrolyte membrane is 80 μm to 300 μm.

[0052] In the present application, the solid electrolyte membrane further includes a binder.

[0053] It is understandable that the present application does not specifically limit the type of binder, and any known binder can be used in the present application without violating the inventive concept of the present application. As an illustrative example only, and not a limitation on the protection scope of the present application, the binder includes but is not limited to one or more of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyvinylidene fluoride hexafluoropropylene (PVDF-HFP), polypropylene (PP), polyethylene (PE), styrene-butadiene rubber (SBR), nitrile rubber (NBR), sodium carboxymethyl cellulose (CMC), polyacrylic acid, polyacrylonitrile, and sodium alginate.

[0054] A second aspect of the present application provides a method for preparing a solid electrolyte membrane, comprising the following steps:

[0055] S1: preparing a first electrolyte.

[0056] S2: preparing the second electrolyte: weighing LiCl, MF3, and NF3, adding them into a ball mill, and forming the second electrolyte by ball milling.

[0057] S3: preparing mixed electrolyte powder: weighing the first electrolyte and the second electrolyte, and ball milling to form mixed electrolyte powder.

[0058] S4: Preparation of solid electrolyte membrane: Mixed electrolyte powder is loaded into a mold and pressed to form a solid electrolyte membrane.

[0059] Specifically, in step S1, the first electrolyte includes Li2ZrCl6 and a derivative of Li2ZrCl6.

[0060] In the raw material MF3 used in step S2, M includes one of Al and In; in the NF3, N includes Ga.

[0061] In step S2, LiCl, MF3, and NF3 are weighed in a molar ratio of (15-35): (0-7): (3-10).

[0062] In step S2, the ball milling jar includes a tungsten carbide ball milling jar.

[0063] In step S2, the mass ratio of the ball milling beads used in the ball mill to the raw material is 15:1-60:1; including but not limited to 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1, 50:1, 55:1, 60:1; preferably, the mass ratio of the ball milling beads used in the ball mill to the raw material is 20-50:1; more preferably, the mass ratio of the ball milling beads used in the ball mill to the raw material is 20-30:1.

[0064] In step S2, the rotation speed of the ball mill is 200r / min~700r / min; including but not limited to 200r / min, 250r / min, 300r / min, 350r / min, 400r / min, 450r / min, 500r / min, 550r / min, 600r / min, 650r / min, 700r / min; preferably, the rotation speed of the ball mill is 200r / min~500rpm; more preferably, the rotation speed of the ball mill is 300r / min~500rpm.

[0065] In step S2, the ball milling time is 2h~24h; including but not limited to 2h, 4h, 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h; preferably, the ball milling time is 2h~12h; more preferably, the ball milling time is 3h~6h.

[0066] In step S3, the mass ratio of the first electrolyte to the second electrolyte is (1-50): (50-99); including but not limited to 1:99, 2:98, 5:95, 10:90, 15:85, 20:80, 25:75, 30:70, 35:65, 40:60, 45:55, 50:50; preferably, the mass ratio of the first electrolyte to the second electrolyte is (5-50): (50-95), more preferably, the mass ratio of the first electrolyte to the second electrolyte is (20-50): (50-80).

[0067] In step S3, the ball milling can be performed in the same manner as step S2, and therefore, it will not be described in detail.

[0068] Specifically, in step S4, the mixed electrolyte powder is loaded into a mold and subjected to tableting to form a solid electrolyte membrane.

[0069] A third aspect of the present application provides a lithium-ion battery, which includes the solid electrolyte membrane provided by the first aspect or the solid electrolyte membrane prepared according to the preparation method provided by the second aspect.

[0070] In some embodiments, the lithium-ion battery includes a positive electrode, a negative electrode and a solid electrolyte membrane arranged between the positive electrode and the negative electrode, wherein the positive electrode plate includes a positive electrode material, and the active material layer of the positive electrode material is composed of 95wt% NCM333, 3wt% PTFE and 2wt% Super-P; the negative electrode plate includes a negative electrode active material, and the negative electrode active material includes metallic lithium.

[0071] The following are specific embodiments.

[0072] Example 1

[0073] This embodiment provides a solid electrolyte membrane, including a first electrolyte and a second electrolyte, wherein the first electrolyte is Li2ZrCl6 and the second electrolyte is Li2Al 0.3 Ga 0.7 Cl2F3, the mass ratio of the first electrolyte to the second electrolyte is 80:20.

[0074] This embodiment provides a method for preparing the above-mentioned solid electrolyte membrane, comprising the following steps:

[0075] S1. Prepare the first electrolyte: weigh anhydrous lithium chloride and anhydrous zirconium chloride in a molar ratio of 2:1, mix them, add them to a ball mill, and mill them at a mass ratio of ball mill beads to the above raw materials of 30:1 at 500 r / min for 6 h to form the first electrolyte Li2ZrCl6.

[0076] S2. Preparation of the second electrolyte: LiCl, AlF3, and GaF3 were weighed in a molar ratio of 20:3:7, added to a ball mill, and the mass ratio of ball mill beads to the above raw materials was 30:1. The ball mill was milled at 500 r / min for 6 h to form the second electrolyte Li2Al 0.3 Ga 0.7 Cl2F3.

[0077] S3. Preparation of composite electrolyte: The first electrolyte and the second electrolyte are weighed and put into a ball mill at a mass ratio of 80:20, and the mass ratio of ball mill beads to the above raw materials is 30:1, and the mixture is ball milled at 200 r / min for 1 h to form a mixed electrolyte powder.

[0078] S4. Preparation of composite electrolyte membrane: The mixed electrolyte powder is placed into a mold and pressed at a pressure of 1.5 T for 1 min to form a solid electrolyte membrane.

[0079] This embodiment provides a battery prepared using the above solid electrolyte membrane, comprising a positive electrode, a negative electrode and the above solid electrolyte membrane. The lithium ion battery assembly method is: aligning and stacking the solid electrolyte membrane and the positive electrode sheet, rolling them, and then attaching the negative electrode sheet to the side of the composite solid electrolyte membrane where the positive electrode sheet is not rolled, and after assembly, a lithium ion battery is obtained.

[0080] Example 2

[0081] The difference between Example 2 and Example 1 is only that the mass ratio of the first electrolyte to the second electrolyte is different.

[0082] This embodiment provides a solid electrolyte membrane, including a first electrolyte and a second electrolyte, wherein the first electrolyte is Li2ZrCl6 and the second electrolyte is Li2Al 0.3 Ga 0.7 Cl2F3, the mass ratio of the first electrolyte to the second electrolyte is 50:50.

[0083] This embodiment provides a method for preparing the above-mentioned solid electrolyte membrane, comprising the following steps:

[0084] S1. Prepare the first electrolyte: weigh anhydrous lithium chloride and anhydrous zirconium chloride in a molar ratio of 2:1, mix them, add them to a ball mill, and mill them at a mass ratio of ball mill beads to the above raw materials of 30:1 at 500 r / min for 6 h to form the first electrolyte Li2ZrCl6.

[0085] S2. Preparation of the second electrolyte: LiCl, AlF3, and GaF3 were weighed in a molar ratio of 20:3:7, added to a ball mill, and the mass ratio of ball mill beads to the above raw materials was 30:1. The ball mill was milled at 500 r / min for 6 h to form the second electrolyte Li2Al 0.3 Ga 0.7 Cl2F3.

[0086] S3. Preparation of mixed electrolyte powder: weigh the first electrolyte and the second electrolyte in a mass ratio of 50:50, put them into a ball mill, and mill at a mass ratio of ball mill beads to the above raw materials of 30:1 at 200 r / min for 1 hour to form a mixed electrolyte powder.

[0087] S4. Preparation of composite electrolyte membrane: The mixed electrolyte powder is placed into a mold and pressed at a pressure of 1.5 T for 1 min to form a solid electrolyte membrane.

[0088] The lithium-ion battery prepared by using the solid electrolyte membrane comprises a positive electrode, a negative electrode and the solid electrolyte membrane.

[0089] The assembly method of the lithium-ion battery is as follows: align and stack the solid electrolyte membrane and the positive electrode sheet, roll them, and then attach the negative electrode sheet to the side of the composite solid electrolyte membrane where the positive electrode sheet is not rolled. After assembly, a lithium-ion battery is obtained.

[0090] Example 3

[0091] The difference between Example 3 and Example 1 is only that the mass ratio of the first electrolyte to the second electrolyte is different.

[0092] This embodiment provides a solid electrolyte membrane, including a first electrolyte and a second electrolyte, wherein the first electrolyte is Li2ZrCl6 and the second electrolyte is Li2Al 0.3 Ga 0.7 Cl2F3, the mass ratio of the first electrolyte to the second electrolyte is 95:5.

[0093] This embodiment provides a method for preparing the above-mentioned solid electrolyte membrane, comprising the following steps:

[0094] S1. Prepare the first electrolyte: weigh anhydrous lithium chloride and anhydrous zirconium chloride in a molar ratio of 2:1, mix them, add them to a ball mill, and mill them at a mass ratio of ball mill beads to the above raw materials of 30:1 at 500 r / min for 6 h to form the first electrolyte Li2ZrCl6.

[0095] S2. Preparation of the second electrolyte: LiCl, AlF3, and GaF3 were weighed in a molar ratio of 20:3:7, added to a ball mill, and the mass ratio of ball mill beads to the above raw materials was 30:1. The ball mill was milled at 500 r / min for 6 h to form the second electrolyte Li2Al 0.3 Ga 0.7 Cl2F3.

[0096] S3, preparing a composite electrolyte: weighing the first electrolyte and the second electrolyte in a ball milling device at a mass ratio of 95:5, and milling at 200 r / min for 1 h at a mass ratio of ball milling beads to the above raw materials of 30:1 to form a composite electrolyte;

[0097] S4. Preparation of composite electrolyte membrane: Place into a mold and press at a pressure of 1.5T for 1 min to form a solid electrolyte membrane.

[0098] A battery prepared using the solid electrolyte membrane comprises a positive electrode, a negative electrode and the solid electrolyte membrane.

[0099] The assembly method of the lithium-ion battery is as follows: align and stack the solid electrolyte membrane and the positive electrode sheet, roll them, and then attach the negative electrode sheet to the side of the composite solid electrolyte membrane where the positive electrode sheet is not rolled. After assembly, a lithium-ion battery is obtained.

[0100] Example 4

[0101] The difference between Example 4 and Example 1 is that the first electrolyte is different from the second electrolyte. The first electrolyte is Li 1.9 Nb 0.1 Zr 0.9 Cl6, the second electrolyte is Li3In 0.6 Ga 0.4 Cl3F3.

[0102] This embodiment provides a solid electrolyte membrane, including a first electrolyte and a second electrolyte, wherein the first electrolyte is Li 1.9 Nb 0.1 Zr 0.9 Cl6, the second electrolyte is Li3In 0.6 Ga 0.4 Cl3F3, the mass ratio of the first electrolyte to the second electrolyte is 80:20.

[0103] This embodiment provides a method for preparing the above-mentioned solid electrolyte membrane, comprising the following steps:

[0104] S1. Preparation of the first electrolyte: Anhydrous lithium chloride, anhydrous zirconium chloride, and anhydrous niobium chloride were weighed and mixed in a molar ratio of 19:9:1, added to a ball mill, and the mass ratio of ball mill beads to the above raw materials was 30:1. The mixture was ball milled at 500 r / min for 6 h to form the first electrolyte Li 1.9 Nb 0.1 Zr 0.9 Cl6.

[0105] S2. Preparation of the second electrolyte: LiCl, InF3, and GaF3 were weighed in a molar ratio of 30:6:4, added to a ball mill, and the mass ratio of ball mill beads to the above raw materials was 30:1. The ball mill was milled at 500 r / min for 6 h to form the second electrolyte Li3In 0.6 Ga 0.4 Cl3F3.

[0106] S3, preparing mixed electrolyte powder: according to the mass ratio of the first electrolyte to the second electrolyte being 80:20, the first electrolyte and the second electrolyte are weighed and put into a ball milling device, and the mass ratio of the ball milling beads to the above raw materials is 30:1, and the mixture is ball milled at 200 r / min for 1 hour to form a mixed electrolyte powder;

[0107] S4. Preparation of composite solid electrolyte membrane: The mixed electrolyte powder is placed into a mold and pressed at a pressure of 1.5 T for 1 min to form a solid electrolyte membrane.

[0108] The lithium-ion battery prepared by using the solid electrolyte membrane comprises a positive electrode, a negative electrode and the solid electrolyte membrane.

[0109] The assembly method of the lithium-ion battery is as follows: align and stack the solid electrolyte membrane and the positive electrode sheet, roll them, and then attach the negative electrode sheet to the side of the composite solid electrolyte membrane where the positive electrode sheet is not rolled. After assembly, a lithium-ion battery is obtained.

[0110] Example 5

[0111] The only difference between Example 5 and Example 1 is that the first electrolyte and the second electrolyte are different, the first electrolyte is Li3InCl6, and the second electrolyte is Li3GaCl3F3.

[0112] This embodiment provides a solid electrolyte membrane, including a first electrolyte and a second electrolyte, wherein the first electrolyte is Li3InCl6, the second electrolyte is Li3GaCl3F3, and the mass ratio of the first electrolyte to the second electrolyte is 80:20.

[0113] This embodiment provides a method for preparing the above-mentioned solid electrolyte membrane, comprising the following steps:

[0114] S1. Prepare the first electrolyte: weigh anhydrous lithium chloride and anhydrous indium chloride in a molar ratio of 3:1, mix them, add them to a ball mill, and mill them at a mass ratio of ball mill beads to the above raw materials of 30:1 at 500 r / min for 6 h to form the first electrolyte Li3InCl6.

[0115] S2. Preparation of the second electrolyte: LiCl and GaF3 were weighed in a molar ratio of 30:10, added into a ball mill, and the mass ratio of ball mill beads to the above raw materials was 30:1. The ball mill was performed at 500 r / min for 6 h to form the second electrolyte Li3GaCl3F3.

[0116] S3, preparing mixed electrolyte powder: according to the mass ratio of the first electrolyte to the second electrolyte of 80:20, weigh the first electrolyte and the second electrolyte into a ball mill, according to the mass ratio of the ball milling beads to the above raw materials of 30:1, at 200r / min, for 1h to form a composite electrolyte;

[0117] S4. Preparation of composite electrolyte membrane: The mixed electrolyte powder is placed into a mold and pressed at a pressure of 1.5 T for 1 min to form a solid electrolyte membrane.

[0118] The lithium-ion battery prepared by using the solid electrolyte membrane comprises a positive electrode, a negative electrode and the solid electrolyte membrane.

[0119] The assembly method of the lithium-ion battery is as follows: align and stack the solid electrolyte membrane and the positive electrode sheet, roll them, and then attach the negative electrode sheet to the side of the composite solid electrolyte membrane where the positive electrode sheet is not rolled. After assembly, a lithium-ion battery is obtained.

[0120] Comparative Example 1

[0121] The difference between Comparative Example 1 and Example 1 is that the second electrolyte is not included but only the first electrolyte is included.

[0122] This comparative example provides a solid electrolyte membrane, comprising a first electrolyte, wherein the first electrolyte is Li2ZrCl6.

[0123] This comparative example provides a method for preparing the above-mentioned solid electrolyte membrane, comprising the following steps:

[0124] S1. Prepare the first electrolyte: weigh anhydrous lithium chloride and anhydrous zirconium chloride in a molar ratio of 2:1, mix them, add them to a ball mill, and mill them at a mass ratio of ball mill beads to the above raw materials of 30:1 at 500 r / min for 6 h to form the first electrolyte Li2ZrCl6.

[0125] S2. Put the first electrolyte into a ball mill, and mill at 200 r / min for 1 h according to the mass ratio of ball mill beads to the above raw materials of 30:1 to form electrolyte powder.

[0126] S3. Preparation of solid electrolyte membrane: electrolyte powder is placed into a mold and pressed at a pressure of 1.5 T for 1 min to form a solid electrolyte membrane.

[0127] The lithium-ion battery prepared by using the solid electrolyte membrane comprises a positive electrode, a negative electrode and the solid electrolyte membrane.

[0128] The assembly method of the lithium-ion battery is as follows: align and stack the solid electrolyte membrane and the positive electrode sheet, roll them, and then attach the negative electrode sheet to the side of the composite solid electrolyte membrane where the positive electrode sheet is not rolled. After assembly, a lithium-ion battery is obtained.

[0129] Comparative Example 2

[0130] The difference between Comparative Example 2 and Example 1 is that the second electrolyte is different. The second solid electrolyte of Comparative Example 2 is Li3YCl6.

[0131] This comparative example provides a solid electrolyte membrane, comprising a first electrolyte and a second electrolyte, wherein the first electrolyte is Li2ZrCl6, the second electrolyte is Li3YCl6, and the mass ratio of the first electrolyte to the second electrolyte is 80:20.

[0132] This embodiment provides a method for preparing the above-mentioned solid electrolyte membrane, comprising the following steps:

[0133] S1. Prepare the first electrolyte: the first electrolyte is Li2ZrCl6.

[0134] S2. Preparation of the second electrolyte Li3YCl6: LiCl (purity: 99.99%) and YCl3 (purity: 99.99%) were weighed and mixed in a molar ratio of 3:1, and added into a ball mill. Under inert gas, the mixture was milled at 500 r / min for 6 h at a mass ratio of ball mill beads to the above raw materials of 30:1 to form the second electrolyte Li3YCl6.

[0135] S3, preparing mixed electrolyte powder: according to the mass ratio of the first electrolyte to the second electrolyte being 80:20, the first electrolyte and the second electrolyte are weighed and put into a ball milling device, and the mass ratio of the ball milling beads to the above raw materials is 30:1, and the mixture is ball milled at 200 r / min for 1 hour to form a mixed electrolyte powder;

[0136] S4. Preparation of composite electrolyte membrane: The mixed electrolyte powder is placed into a mold and pressed at a pressure of 1.5 T for 1 min to form a solid electrolyte membrane.

[0137] The battery prepared using the above solid electrolyte membrane comprises a positive electrode, a negative electrode and the above solid electrolyte membrane. The assembly method of the lithium-ion battery is as follows: the solid electrolyte membrane and the positive electrode sheet are aligned and stacked, and after rolling, the negative electrode sheet is attached to the side of the composite solid electrolyte membrane where the positive electrode sheet is not rolled, and after assembly, a lithium-ion battery is obtained.

[0138] Test Case

[0139] (1) Conductivity test of electrolyte membrane

[0140] At room temperature, the solid electrolyte membranes obtained in Examples 1 to 5 and Comparative Examples 1 to 2 were connected to an electrochemical workstation for impedance testing. The final conductivity was calculated according to the formula σ = I / (AR). The data are summarized in Table 1; wherein σ is conductivity in S / cm, I is the average thickness of the solid electrolyte membrane in cm, and A is the area of ​​the solid electrolyte membrane in cm. 2 ; R is the body impedance of the solid electrolyte membrane, in Ω. The test results are shown in Table 1 below.

[0141] (2) Porosity test of electrolyte membrane

[0142] The porosity of the solid electrolyte membranes of Examples 1 to 5 and Comparative Examples 1 to 2 was tested using an SSA-4200 pore size and specific surface area analyzer. The test results are shown in Table 1 below.

[0143] (3) Battery test

[0144] Battery preparation: Prepare the solid electrolyte membranes prepared in Examples 1 to 5 and Comparative Examples 1 to 2 respectively; evenly disperse 7 mg of composite positive electrode powder on one side of the solid electrolyte membrane, apply 2.4 T pressure and hold the pressure for 3 minutes to achieve close contact between the positive electrode and the electrolyte. Among them, the mass ratio of active material, electrolyte and conductive carbon in the composite positive electrode powder is 40:57:3, the diameter of the composite positive electrode layer is 10 mm, and the thickness after compaction is about 40 μm. Next, 35 mg of LPSCl (lithium phosphorus sulfur chloride) powder is evenly dispersed on the side of the solid electrolyte membrane where the composite positive electrode powder is not dispersed, and a pressure of 1.2 T is applied and the pressure is held for 1 minute. The diameter of the LPSCl layer is 10 mm, and the thickness after compaction is about 180 μm. Finally, an indium sheet with a diameter of 10 mm and a thickness of 0.5 mm and a lithium sheet with a diameter of 10 mm and a thickness of 0.15 mm are added to the LPSCl layer in sequence, and a pressure of 1.2 T is applied and the pressure is held for 1 minute to form a lithium-indium alloy. After forming, the alloy sheet has a diameter of 10 mm and a thickness of about 600 μm. The metal frame is added to assemble the battery, and the EIS test, LCO battery discharge capacity test and battery cycle performance test are carried out under an external constant voltage of 1.5 T.

[0145] (3-1) Battery internal resistance test

[0146] After the battery was prepared using the above method, the internal resistance was measured using a voltage internal resistance meter. The test results are shown in Table 1.

[0147] (3-2) LCO battery discharge capacity test

[0148] After the battery was prepared in the same manner as above, a battery discharge test was performed under the conditions of 25°C, 0.05C current, and a discharge cut-off voltage of 0.005V-2.0V. The results are shown in Table 1.

[0149] (3-3) Battery cycle performance test

[0150] The assembled battery was charged and discharged in the voltage range of 3-4.2V, with a rate of 0.05C for the first two cycles and a rate of 0.1C from the third cycle onwards. The cycle was cycled to the 50th cycle and the cycle retention rate was recorded. The cycle retention rate = discharge capacity at the 50th cycle / discharge capacity at the 5th cycle.

[0151] The test data of EIS test, LCO battery discharge capacity test and battery cycle performance test are summarized in Table 1.

[0152]

[0153] As can be seen from Table 1 above, the present application forms a continuous phase through the coordination of the first electrolyte and the second electrolyte, and mixes with the first electrolyte, thereby improving the compactness of the solid electrolyte membrane, reducing the porosity of the electrolyte membrane, and further improving the conductivity of the electrolyte membrane. The cycle performance of the prepared battery is significantly improved, and the internal resistance of the battery is further reduced. At the same time, it can be seen from Comparative Example 1 that when there is only the first solid electrolyte, the porosity of the solid electrolyte membrane is significantly increased, while the conductivity is significantly decreased, and the battery cycle performance is reduced to less than 90%. When two halide solid electrolytes are used, the prepared solid electrolyte membrane also has a higher porosity, and its conductivity is also significantly reduced. At the same time, the internal resistance of the battery increases, and the cycle performance is significantly reduced compared to the embodiment of the present application.

[0154] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0155] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A solid electrolyte membrane, characterized in that: The solid electrolyte membrane comprises a first electrolyte and a second electrolyte; wherein, The first electrolyte includes or A derivative of; the Young's modulus of the first electrolyte is less than 100 GPa; The liquid index of the second electrolyte is greater than 1; Under the same pressure, the volume deformation of the first electrolyte is smaller than the volume deformation of the second electrolyte; The ionic conductivity of the second electrolyte is greater than the ionic conductivity of the first electrolyte; The second electrolyte includes , wherein 1.5≤a:b≤3.5, 0<m<0.7, M includes one of Al and In, and N includes Ga; The ionic conductivity of the first electrolyte satisfies ; The ionic conductivity of the second electrolyte satisfies .

2. The solid electrolyte membrane according to claim 1, characterized in that The Young's modulus of the first electrolyte is less than 45 GPa.

3. The solid electrolyte membrane according to claim 1, characterized in that The porosity φ of the solid electrolyte membrane is less than 10%.

4. The solid electrolyte membrane according to claim 1, characterized in that Said Derivatives include ; Wherein, a is the valence state of metal A, 1≤a≤6, x<1, and metal A includes one of Dy, Nb, and Mn; or, Derivatives include ; Wherein, b is the valence state of metal B, y≤1, and B is O element or halogen element.

5. A method for preparing a solid electrolyte membrane according to any one of claims 1 to 4, characterized in that: The following steps are involved: preparing a first electrolyte; Prepare the second electrolyte: weigh , , , added into a ball mill, and formed a second electrolyte through ball milling; Prepare mixed electrolyte powder: weigh the first solid electrolyte and the second solid electrolyte, and ball-mill them to form mixed electrolyte powder; Preparation of solid electrolyte membrane: Mixed electrolyte powder is loaded into a mold and pressed to form a solid electrolyte membrane; Said wherein M includes one of Al and In; In, N includes Ga; In the mixed electrolyte powder, the mass ratio of the first electrolyte to the second electrolyte is (1-50):(50-99).

6. A lithium ion battery, characterized in that: The lithium-ion battery comprises the solid electrolyte membrane according to any one of claims 1 to 4 or the solid electrolyte membrane prepared by the method according to claim 5.

Citation Information

Patent Citations

  • Solid electrolyte and battery using same

    CN112602222A